Electrical transport across nanometric SrTiO3 and BaTiO3 barriers in conducting/insulator/conducting junctions - Navarro, H.; Sirena, M.; González Sutter, J.; Troiani, H.E.; del Corro, P.G.; Granell, P.; Golmar, F.; Haberkorn, N.; Haberkorn, Néstor (IOP Publishing, 2018)
Fil: Navarro, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina